2004
DOI: 10.1007/s00253-003-1294-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aspergillus oryzae fermentation extract effects on the rumen fungus Neocallimastix frontalis , EB 188. Part 2. Carbon source utilization and effects on zoospore production

Abstract: The effect of a commercial Aspergillus oryzae fermentation extract on the utilization of carbon source and zoospore production by the rumen fungus Neocallimastix frontalis EB 188 was determined. In addition, the composition of a soluble extract prepared from the commercial product was analyzed. This extract was added to N. frontalis EB 188 cultures grown on a variety of substrates and periodically assayed for protein, enzymes, zoospore production, and carbon source utilization. The powdered product contained 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In addition, there were interactions between HMB and AOC in fungi and R. flavefaciens of CWR and in R. albus of CS. The larger HMB×AOC effects on fungi and R. flavefaciens with AOC could partly be explained by Schmidt et al (2004) who found that AOC accelerated the production and maturation of zoospores of Neocallimastix frontalis EB 188, along with an elevated production of protein and carboxymethy cellulase (CMCase). The mechanisms by which these supplements could impact microbial digestion in the rumen have not yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were interactions between HMB and AOC in fungi and R. flavefaciens of CWR and in R. albus of CS. The larger HMB×AOC effects on fungi and R. flavefaciens with AOC could partly be explained by Schmidt et al (2004) who found that AOC accelerated the production and maturation of zoospores of Neocallimastix frontalis EB 188, along with an elevated production of protein and carboxymethy cellulase (CMCase). The mechanisms by which these supplements could impact microbial digestion in the rumen have not yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used as a prebiotic in calf feed (Beharka et al, 1991), but has more commonly been used in sheep and beef finishing diets (Schmidt et al, 2004;Zerby et al, 2011). Aspergillus oryzae has long been used in the Japanese food industry for fermenting foods such as saki, soy sauce, and miso, and it is regarded as safe because it does not produce aflatoxin (Uchida et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…(2000) found that a preparation containing enzymes increased the degradability of dry matter and increased ruminal fluid CMCase activity. Schmidt et al. (2004) reported that extracts of Ao accelerated the production and maturation of zoospores of Neocallimastix frontalis EB 188, with an elevated production of protein and CMCase activity.…”
Section: Discussionmentioning
confidence: 99%
“…(2004), for the addition of a culture of the rumen anaerobic fungus Piromyces communis strain 22 to mixed ruminal micro‐organisms in vitro. In addition, Schmidt et al. (2004) reported that Ao had unidentified components or factors, which were responsible for the stimulation of the zoospore production of the rumen fungus Neocallimastix frontalis EB 188.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation